OLIVEIRA, R. R. (2013). Pólis e Nómos:: o problema da lei no pensamento grego. São Paulo: Editora Loyola. (Revista Archai, 2014)
OLIVEIRA, R. R. (2013). Pólis e Nómos: o problema da lei no pensamento grego. São Paulo: Editora Loyola.